2010
DOI: 10.1007/s11095-010-0150-6
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Artificial Membrane Permeation Assay under Hydrodynamic Control: Permeability-pH Profiles of Warfarin and Verapamil

Abstract: Both warfarin and verapamil exhibit high permeability values, which is consistent with the high fraction absorbed in human. Our results demonstrate that a considerable lag-time, varying with the solute lipophilicity and stirring rate, exists in membrane permeation and leads to incorrect compound ranking if it is not treated properly. Comparison of the permeability data as a function of pH and stirring rate suggests that some transport of the ionized molecules occurs, most likely via ion-pairing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 44 publications
1
35
0
2
Order By: Relevance
“…Warfarin, in contrast, diffuses freely in and out of the DPPC interface, in agreement with the behavior of deprotonated warfarin in atomistic simulations 44 . Lateral diffusion of both warfarin and brodifacoum occurs with a diffusivity on the order of 10 -6 cm 2 /s, comparing favorably with the membrane diffusion coefficient value of 1.611 ± 0.164 ×10 -6 cm 2 /s determined by artificial membrane permeation assay for warfarin 45 . We are not aware of any similar experimental measure for the much more rarely studied compound, brodifacoum, however, our diffusivity values for both species are comparable to experimental diffusion measurements for other small molecules 88, 89 .…”
Section: Structural Perturbation Of Dppc Bilayers Induced By Hydroxycsupporting
confidence: 67%
“…Warfarin, in contrast, diffuses freely in and out of the DPPC interface, in agreement with the behavior of deprotonated warfarin in atomistic simulations 44 . Lateral diffusion of both warfarin and brodifacoum occurs with a diffusivity on the order of 10 -6 cm 2 /s, comparing favorably with the membrane diffusion coefficient value of 1.611 ± 0.164 ×10 -6 cm 2 /s determined by artificial membrane permeation assay for warfarin 45 . We are not aware of any similar experimental measure for the much more rarely studied compound, brodifacoum, however, our diffusivity values for both species are comparable to experimental diffusion measurements for other small molecules 88, 89 .…”
Section: Structural Perturbation Of Dppc Bilayers Induced By Hydroxycsupporting
confidence: 67%
“…Permeation through the ABL is by passive diffusion. Hence, the ABL is a rate-limiting step for permeation of lipophilic compounds resulting in reduction of the apparent permeability (Hidalgo et al, 1991;Karlsson and Artursson, 1991;Ruell et al, 2003;Avdeef et al, 2004;Katneni et al, 2008;Velický et al, 2010), leading to reduced dynamic range and lower resolution in rank-ordering compound permeation. The ABL can also be a source of bias in determining the Michaelis-Menten transport kinetic K m because of the concentration gradient created within the ABL (Wilson and Dietschy, 1974;Balakrishnan et al, 2007) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that controlled hydrodynamics or stirring of the membrane improved the predictive power of in vitro permeability assays, thus mimicking the diffusion/convection conditions in a human intestine [69,70]. The traditional view of the widely accepted pH-partition hypothesis has also been challenged using a hydrodynamic approach to permeability [71]. It is interesting to note that several research groups independently pursued studies on the electrochemical response of SLM systems under hydrodynamic control.…”
Section: Voltammetry In Membrane Permeability Studiesmentioning
confidence: 99%